Demand for regional level III neonatal services is not reduced during national COVID lockdowns. (December 2021) - Kenney, I.; Maalouf, N.; Adams, G.; Grayson, K.; Brown, N.; Howarth, C.N.; Aladangady, N.; Fleming, P.F.
Abstract: Following the first peak of the COVID-19 pandemic, reports from around the world suggested a reduction in preterm deliveries during lockdown periods. We reviewed preterm admissions to a large tertiary neonatal unit in inner North East London during two United Kingdom (UK) national lockdowns in 2020 and 2021. We found no evidence of difference in admissions during two national lockdowns compared to previous years. Based on these findings, we recommend that neonatal services remain as vigilant and prepared as ever for the unpredictable nature of preterm birth, and their staff protected to provide this highly specialist care. Highlights: Since the beginning of the COVID-19 pandemic, inconsistent reports of falling preterm births have emerged from around the world We analysed admission rates for preterm babies to a large regional neonatal service over two national lockdowns Preterm admissions were no different during two national lockdowns when compared to previous years